Formation strategies of mixed flow with connected and automated multi-type vehicles based on an improved Markov chain model - ZHAO Zheng; PANG Mingbao (Shenzhen Daxue xuebao. Ligong ban)
To enhance the roadway capacity of mixed traffic flow with connected and automated (CA) trucks and cars as well as manually driven trucks and cars, we propose strategies for individual and cooperative vehicle formations for CA vehicles based on platooning intensity and permeability. Two vehicle following modes of mixed-flow are designed for each strategy, respectively. The vehicle state transfer probabilities are derived using an improved Markov chain model, where CA vehicles permeability and platooning intensity are considered. Then, platooning distributions of two strategies are discussed and road capacity models for mixed traffic flow are established. The effectiveness of these strategies is validated through theoretical proofs and simulation experiments. Results show that compared to no-formation strategies, both individual and cooperative formation strategies can increase road capacity by 1.23% to 49.62% and 1.47% to 60.34%, respectively. The cooperative formation strategy further enhances road capacity by an additional 11% compared to the individual formation strategy. When CA vehicle permeability is larger than 50% and platooning intensity is above zero, road capacity can be significantly enhanced with the increasement (13.27%～60.34%) of the maximum platooning size. Under the individual formation strategy, maximum platooning sizes are 8 vehicles for CA cars and 6 vehicles for CA trucks, while under the cooperative formation strategy, the maximum platooning size for CA vehicles reaches 8.